Tinjauan Ketepatan Kode Diagnosa Gastroenteritis pada Pasien Rawat Inap di Rumah Sakit Umum Daerah Budhi Asih - Hudiyati Agustini; Fathirsa Ariya Wirayuda; Indah Kristina (APIKES Bhumi Husada Jakarta, 2023)
The results of early observations at the Budhi Asih Hospital, on the medical record files of inpatients with a diagnosis of gastroenteritis, found that there were still coding errors. The Gastroenteric Code is divided into two, namely infectious gastroenteritis and non-infectious gastroenteritis. Infectious gastroenteritis can be coded A09.0 (acute infectious gastroenteritis) or A09.9 (unspecified infectious gastroenteritis). Meanwhile, non-infectious gastroenteritis can be coded K52.- and non-infectious gastroenteritis in neonates is coded P78.3. The completeness and accuracy of gastroenteritis coding comes from doctors and nurses who record information on the patient's condition, as well as coding officers providing coding. The purpose of this study was to determine the completeness and accuracy of coding in cases of gastroenteritis in hospitalized patients based on ICD-10. Keywords: Diagnostic code accuracy, Gastroenteritis, Discharge Summary.